Feasibility of a social protection linkage program for individuals at-risk for tuberculosis in Uganda. - Grace Nanyunja; Jillian L Kadota; Catherine Namale; Mollie Hudson; Talemwa Nalugwa; Stavia Turyahabwe; Adithya Cattamanchi; Achilles Katamba; Prosper Muhumuza; Priya B Shete (Public Library of Science (PLoS), 2023)
Social protection interventions have the potential to accelerate progress towards global tuberculosis (TB) targets. We piloted a screening and linkage program at four community health centers (HC) to enroll adults seeking TB diagnostic evaluation services into existing government-supported social protection programs in Uganda. From May-December 2021, health center staff were asked to screen adults being evaluated for TB for eligibility for government-supported social protection programs, and to refer eligible people to a sub-county community development office (CDO) responsible for enrolling community members into government-supported social protection programs. Linkage was facilitated with a transportation reimbursement via mobile money and referral documentation confirming program eligibility. We assessed feasibility using programmatic data and conducted post-intervention surveys to understand experiences with the linkage program. Of 855 people undergoing TB evaluation, 655 (76%) adults met criteria for at least one government-supported social protection program. 25 (4%) of those were not interested in referral; the rest were referred to their local CDO. While 386 (61%) of the 630 participants reported to the CDO seeking social protection enrolment, only 122 (32%) of those were ultimately enrolled into a social protection scheme, representing only 19% (n = 655) of those eligible. In surveys conducted among 97 participants, 46 of the 60 (77%) people who reported that they sought enrollment at the CDO were not enrolled into a social protection program. Reasons provided for non-enrollment among these 46 participants were either unknown (n = 25, 54%) or due to operational challenges at the CDO including a lack of human resources or available groups to join in the social protection program (n = 20, 43%). 61 survey participants (63%) indicated that they would not have sought social protection enrollment without the referral program. Overall, we found that most adults seeking TB diagnostic evaluation are eligible for and interested in obtaining government-supported social protection. We found facilitated linkage from HCs to CDOs offering social protection services to be feasible, however ultimate enrollment into programs was limited. Additional research is needed to identify strategies to improve access to existing social protection programs for eligible TB-affected individuals. Trial Registration: Pan African Clinical Trials Registry (PACTR201906852160014).